2008
DOI: 10.1139/f08-123
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen concentration in the water boundary layer next to rainbow trout (Oncorhynchus mykiss) embryos is influenced by hypoxia exposure time, metabolic rate, and water flow

Abstract: The objective of this study was to examine the influence of hypoxia exposure time, metabolic rate, and water flow rate on the O2 concentration in the boundary layer outside and inside the chorion of rainbow trout ( Oncorhynchus mykiss ) embryos. Oxygen consumption, growth, and dissolved O2 in the boundary layer were measured at 15, 22, and 29 days post fertilization (dpf) from embryos reared in normoxia (O2 concentration at 100% saturation) and chronic hypoxia (>24 h, 50% saturation) and exposed to acute hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 23 publications
4
29
0
Order By: Relevance
“…We propose that the lower metabolic rate in the terrestrial environment is related in part to fewer opercular movements. In encapsulated fish embryos, relatively thick boundary layers develop in low flow environments that may impair oxygen transport in aquatic environments (Ciuhanda et al, 2007;Miller et al, 2008;Dhiyebi et al, 2013). We found evidence to support the hypothesis that embryos manipulate their micro-environment to maintain oxygen delivery.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We propose that the lower metabolic rate in the terrestrial environment is related in part to fewer opercular movements. In encapsulated fish embryos, relatively thick boundary layers develop in low flow environments that may impair oxygen transport in aquatic environments (Ciuhanda et al, 2007;Miller et al, 2008;Dhiyebi et al, 2013). We found evidence to support the hypothesis that embryos manipulate their micro-environment to maintain oxygen delivery.…”
Section: Discussionsupporting
confidence: 66%
“…Matschak et al, 1997;Barrionuevo and Burggren, 1999;Miller et al, 2008). Hypoxia delays development in fishes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This level of O 2 saturation has been observed previously in salmonid redds (Coble, 1961;Peterson and Quinn, 1996;Youngson et al, 2004) and was shown to significantly affect metabolic rate and cardiac development in embryonic rainbow trout (Miller et al, 2008;Miller et al, 2011). Hypoxia was generated by introducing N 2 gas into a header tank (~16 l).…”
Section: Experimental Protocol Treatment Conditionssupporting
confidence: 52%
“…Dissolved O 2 was monitored daily in the normoxic (98.7±0.4%) and hypoxic (29.7±0.5%) treatment tanks throughout the experiment (Hach LDO101 electrode connected to Hach HQ30d meter, Hach Company, Mississauga, ON, Canada). Because hypoxia exposure delays salmonid development (Shumway et al, 1964;Hamor and Garside, 1976;Ciuhandu et al, 2005;Miller et al, 2008), embryo sampling was stage-matched for the two treatment groups. Embryos were sampled at Vernier Stages 27 (prehatch; circulatory system is formed and functioning), 30 (hatch), 32 and 33 (in preliminary experiments a large increase in P 50 was observed between these stages), and 35 (near-complete yolk absorption; Fig.…”
Section: Experimental Protocol Treatment Conditionsmentioning
confidence: 99%
See 1 more Smart Citation